Effect of Pulmonary-Specific Enteral Nutrition on Neutrophil-to-Lymphocyte Ratio and Blood Lactate Levels in Mechanically Ventilated Pneumonia Patients: A Double-Blind Randomized Controlled Trial - Achmad Mudassir Muchlis (Indonesia Journal of Chest Critical Emergency Medicine, 2026)
Background: Pneumonia remains a major cause of morbidity and mortality, particularly among critically ill patients requiring mechanical ventilation. Systemic inflammation and metabolic dysfunction may be reflected by biomarkers such as neutrophil-to-lymphocyte ratio (NLR) and blood lactate levels. Pulmonary-specific enteral nutrition has been proposed to improve metabolic responses in these patients. This study aimed to evaluate its effect on NLR and blood lactate levels in mechanically ventilated pneumonia patients. Methods: A double-blind randomized controlled trial was conducted in the intensive care and high care units of a tertiary referral hospital in Jakarta, Indonesia. Adult mechanically ventilated pneumonia patients were randomized to receive either pulmonary-specific enteral nutrition or standard enteral nutrition. NLR and blood lactate levels were measured on days 1, 3, and 5. Within-group comparisons were analyzed using the Friedman test, while between-group comparisons were assessed using the Mann–Whitney U test. Results: Of 56 randomized patients, 46 completed the study and were included in the final analysis (24 intervention vs. 22 control). No significant differences in NLR changes were observed between groups during the observation period. However, blood lactate dynamics differed significantly between groups at the day 3–5 interval (p = 0.017) and cumulatively from day 1 to day 5 (p = 0.037), with the intervention group demonstrating a more stable decline in lactate levels. Conclusion: Pulmonary-specific enteral nutrition was associated with improved lactate dynamics, suggesting better metabolic stability in mechanically ventilated pneumonia patients, although no significant effect on NLR was observed. Keywords: Pneumonia; Enteral Nutrition; Mechanical Ventilation; Neutrophil-to-Lymphocyte Ratio; Lactate